Peran Guru TPQ Dalam Meningkatkan Kemampuan Baca Al-Qur'an pada Anak di TPQ As-salafiyah Jogomertan - Ma'unah, Alfi; Rinawati, Atim (IAINU Kebumen, 2026)
Increasingly advanced technological developments have both positive and negative impacts on children, the negative impact for children of learning the Al-Qur’an is that children prefer it spend hours playing on cellphones rather than studying Al-Qur’an. Therefore, the role of TPQ As-Salafiyah Jogomertan is really needed learning the Al-Qur'an because at TPQ the learning method uses a fun method so that children are more enthusiastic about learning the Koran plus habituation activities such as memorizing daily prayers, memorizing short letters, practice ablution and prayer. The purpose of this research is to determine the role of TPQ teachers in improving the quality of Al-Qur'an reading skills in children at TPQ As-Salafiyah.This study used qualitative research methods. Data collection techniques, namely interviews, observations, and documentation. The data analysis used is data reduction, presenting data, and drawing conclusions. The researcher concluded, it can be concluded that the role of TPQ teachers in improving the quality of the ability to read the Al-Qur'an in TPQ As-salafiyah, namely the teacher's role as educator, teacher, guide, director, trainer and evaluator of his students. The teacher gives knowledge about how to do it read the Al-Qur'an properly and correctly according to the rules of tajwid science and methods The learning used is the qira'ati method with classical teaching groups, individuals and sometimes through habituation.